Relationship between Serum Creatine Kinase and Skeletal Muscle Injury in Physical Assault Cases - Adil, Muhammad; Memon, Haya Afzal; Hameed, Aisha; Aftab, Faiza; Mahmood, Madiha; Sajid, Bushra (Journal of Neonatal Surgery, 2025)
Background: Physical assault frequently results in skeletal muscle injury, yet objective biochemical markers that quantify the degree of trauma remain underutilized in forensic evaluations. Serum creatine kinase (CK) is released following muscle fiber damage and may serve as an adjunct indicator of injury severity. Objective: To determine the relationship between serum CK levels and the extent of skeletal muscle injury in victims of non-fatal physical assault. Methods: A cross-sectional study was conducted on 120 adult assault victims presenting to the emergency department of JPMC, Karachi. Serum CK was measured within 6 hours of presentation. Injury severity was graded using a standardized Muscle Injury Score (MIS) based on clinical examination and ultrasound findings. Data were analyzed using SPSS v26. Pearson correlation was used to assess the relationship between CK and MIS. Results: The mean CK level in assault victims was 612 ± 298 U/L (reference: <190 U/L). CK levels showed a significant positive correlation with muscle injury severity (r = 0.71, p < 0.001). Patients with mild, moderate, and severe MIS had mean CK levels of 280 ± 96, 620 ± 160, and 1,120 ± 350 U/L, respectively (p < 0.001). No significant difference in CK levels was observed between age groups or gender. Blunt trauma from sticks and rods produced significantly higher CK levels than fist blows. Conclusion: Serum CK is significantly elevated in victims of physical assault and correlates strongly with the severity of skeletal muscle injury. CK measurement can serve as an objective biochemical marker supporting clinical and forensic assessment of trauma severity..